Tingkat Ketercapaian Tugas Perkembangan Dewasa Awal: Studi Deskriptif pada Mahasiswa IAIN Curup - Dewi Purnama Sari (Islamic Counseling : Jurnal Bimbingan dan Konseling Islam, 2021)
The purpose of this study is to see the level of achievement of student development tasks to be used as a basic reference in providing guidance, assistance and designing activity programs to develop student potential. This research is a quantitative descriptive study that aims to obtain information on the level of achievement of student development tasks at the Tarbiyah Faculty of IAIN Curup. This study involved 30 PAI study program students, 30 PGMI students, 25 BKPI students, 25 English students and 16 PBA students. Data on the level of achievement of student development was collected using the Student Development Task Inventory (ITP-PT) and then analyzed by statistical analysis of percentages. As a result, the average level of achievement of student development tasks is at the individuality level. There are four aspects of development that have reached the stage of autonomy, namely awareness of responsibility achieved by students of the Islamic Religious Education (PAI) study program and students of the Guidance and Counseling (BK) study program. The basic aspects of life achieved by students of the English Language Education (PBI) study program and aspects of self-acceptance and development have also reached the level of autonomy. Following up on the findings of this study, mastery of the level of achievement of student developmental tasks can be optimized through guidance and counseling activities.